2018
DOI: 10.1155/2018/8702605
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Type III Metabolism Evaluation in Patients with Malignant Head and Neck Cancer Treated with Radiotherapy

Abstract: Ionizing radiation affects the metabolism of key proteins of extracellular matrix including type III collagen, an important component of human skin. The aim of the work is an analysis of the impact of radical and palliative radiotherapy on collagen type III synthesis in patients with head and neck cancer. The test group consisted of 56 males with histopathologically confirmed head and neck cancer, for whom radiotherapy was applied as a form of radical or palliative treatment. The level of procollagen III amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Modulations in several types of collagens were a major identifier of the GP6 signaling and the intrinsic prothrombin signaling pathways. The disrupted transcription of different types of collagens identified here was congruent with similar modulations in collagen synthesis in patients treated with radiation for head and neck cancer [ 52 ] or from in vitro experiments using irradiated fibroblasts [ 53 ]. The downregulation of collagens has a multitude of implications on cell biology.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Modulations in several types of collagens were a major identifier of the GP6 signaling and the intrinsic prothrombin signaling pathways. The disrupted transcription of different types of collagens identified here was congruent with similar modulations in collagen synthesis in patients treated with radiation for head and neck cancer [ 52 ] or from in vitro experiments using irradiated fibroblasts [ 53 ]. The downregulation of collagens has a multitude of implications on cell biology.…”
Section: Discussionsupporting
confidence: 76%
“…The downregulation of collagens has a multitude of implications on cell biology. Some of these implications are direct, as seen in the reported changes in skin structure and functions after radiation [ 35 , 52 , 53 , 54 , 55 ], or in the increased bleeding [ 56 , 57 ] upon changes in collagen–platelet interactions, which trigger the activation of platelets and initiate the coagulation cascade. While these interactions were likely to contribute to the mid or late effects of radiation as the transcriptional changes are translated into a modified extracellular matrix structure or composition, immediate impacts of collagen transcription modulations mediated by the intracellular processes associated with or secondary to collagen translation, post-translational modifications, and intracellular assembly and transport occur much earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy can affect fibroblasts within the tissue, leading to overactivation and sometimes increased collagen synthesis. 62 We showed that treated tumor αSMA+ fibroblast numbers increased significantly from Day 0 to Day 6 and collagen density significantly increased at Day 6, possibly reflecting the overactivation effect of radiation therapy on the fibroblasts. However, we also showed a significant decrease in treated tumor αSMA+ fibroblast numbers from Day 6 to Day 9.…”
Section: Discussionmentioning
confidence: 73%
“…In a cohort of male head and neck cancer patients, 20 Gy of radiation therapy led to a decrease in collagen III synthesis. 62 Interestingly, in a cohort of female breast cancer patients who received 50 Gy, the opposite effect was seen following radiation therapy where an increase in collagen I and III synthesis was observed. 64 We presume the collagen imaged within these melanoma tumors is primarily collagen I with some collagen III contribution.…”
Section: Discussionmentioning
confidence: 98%
“…It is also associated with the increased breast density and the over deposition of collagens such as collagen I, II, and III which involved in tumor progression and invasion as it involved in altering tumor stroma structure through series of enzymatic reaction that results in increasing its thickness, stiffness, crosslinking, degradation, redeposition and accordingly altered ECM remodeling and facilitate tumor progression (Fang et al 2014). Collagen III is one of the main fibrillar structural proteins of ECM which comprises 10-15% of skin collagen (Riekki et al 2004;Mazurek et al 2018). Mutation in this collagen involved in several malignancies and it can be used as a biomarker (Nielsen and Karsdal, 2016).…”
Section: Discussionmentioning
confidence: 99%